BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Genealogical concordance, comparative species delimitation, and the specific status of the Caspian pipefish Syngnathus caspius (Teleostei: Syngnathidae) - Fatah Zarei; Hamid Reza Esmaeili; Keyvan Abbasi; Golnaz Sayyadzadeh; Soheil Eagderi; Brian W. Coad (Marine Ecology, 2021)
To evaluate the specific validity of the Caspian pipefish Syngnathus caspius , we used a comparative molecular species delimitation method on a COI barcode library of Syngnathus , as well as principles of genealogical concordance. Comparative species delimitation allowed us to delineate putative species without a priori assignment of individuals to nominal species, while genealogical concordance extended our species delimitation results to multiple genes, multiple codistributed species, and comparisons with biogeographic evidence. All species delimitation analyses including two topology‐based, one network‐based, and one distance‐based analysis showed genetically isolated lineages of pipefish in the Black and Caspian Sea, corresponding to S. abaster and S. caspius , respectively. Mean evolutionary divergence between the two lineages (0.029) was within the range separating species of Syngnathus (0.024–0.217). The interclade/intraclade ratio of variation was comparable to the operational criterion of divergence between clades greater or equal to 10 × the level within clades to recognize separate species. Our argument on taxonomic validity of S. caspius is also supported by the principles of genealogical concordance as a conceptual basis for recognition of biological species. As a second objective, using a limited number of S. caspius specimens from two semi‐confined water bodies along the Caspian Sea south coastal zone (i.e., Anzali Wetland in the west and Gorgan Bay in the east), we searched for a possible matrilineal structure. The retrieved phylogeographic pattern was characterized by a shallow genealogy and lineage distributions varied, most probably caused by low to modest contemporary gene flow between populations of S. caspius across the southern Caspian Sea that are linked tightly through history.

Phylogeographic pattern and population structure of the Persian stone loach, Oxynoemacheilus persa (Heckel 1847) (family: Nemacheilidae) in southern Iran with implications for conservation - Hamid Reza Esmaeili; Golnaz Sayyadzadeh; Fatah Zarei; Sasan Kafaei; Brian W. Coad (Environmental Biology of Fishes, 2020)

Threatened fishes of the world: Acanthobrama hadiyahensis Coad, Alkahem and Behnke, 1983 (Cyprinidae) - Brian W. Coad (Environmental Biology of Fishes, 2010)

Threatened fishes of the world: Luciobarbus subquincunciatus (Günther, 1868) (Cyprinidae) - Brian W. Coad (Environmental Biology of Fishes, 2009)

Threatened fishes of the world: Seminemacheilus tongiorgii Nalbant and Bianco, 1998 (Balitoridae) - H. R. Esmaeili; A. Teimory; Brian W. Coad; Z. Gholami (Environmental Biology of Fishes, 2009)

Threatened fishes of the world: Paracobitis smithi (Greenwood, 1976) (Balitoridae) - Brian W. Coad; R. Mehrani; N. Najafpour (Environmental Biology of Fishes, 2009)

A random process may control the number of endemic species - Boris Ya. Vilenkin; Vladimir I. Chikatunov; Brian W. Coad; Anatoly A. Schileyko (Biologia, 2009)

Threatened fishes of the world: Cobitis linea (Heckel, 1849) (Cobitidae) - H. R. Esmaeili; A. Teimory; Brian W. Coad; Z. Gholami (Environmental Biology of Fishes, 2008)

Fish Imagery in Art 82: Jonah and the Fish - Brian W. Coad; James W. Atz; Yazdan Keivany (Environmental Biology of Fishes, 2000)

Threatened fishes of the world: Lebias ginaonis (Holly, 1929) (Cyprinodontidae) - Brian W. Coad (Environmental Biology of Fishes, 1998)